2018
DOI: 10.1007/s13244-018-0664-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in Fabry disease: current knowledge and future directions

Abstract: Fabry disease (FD) is a rare X-linked disorder characterised by abnormal progressive lysosomal deposition of globotriaosylceramide in a large variety of cell types. The central nervous system (CNS) is often involved in FD, with a wide spectrum of manifestations ranging from mild symptoms to more severe courses related to acute cerebrovascular events. In this review we present the current knowledge on brain imaging for this condition, with a comprehensive and critical description of its most common neuroradiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 93 publications
(104 reference statements)
1
38
2
Order By: Relevance
“…On MRI, white matter lesions are present in 80% of cases and can be heterogenous, ranging from small, scattered and punctuate T2-weighted hyperintense foci to bilateral diffuse, patchy and partly confluent white matter hyperintensities. An important characteristic is that the lesions in Fabry disease only present themselves in the supratentorial white matter, which was not the case in our patient 19 .…”
Section: Hiv-associated Dementia Is Associated With a Symmetrical Pecontrasting
confidence: 48%
See 1 more Smart Citation
“…On MRI, white matter lesions are present in 80% of cases and can be heterogenous, ranging from small, scattered and punctuate T2-weighted hyperintense foci to bilateral diffuse, patchy and partly confluent white matter hyperintensities. An important characteristic is that the lesions in Fabry disease only present themselves in the supratentorial white matter, which was not the case in our patient 19 .…”
Section: Hiv-associated Dementia Is Associated With a Symmetrical Pecontrasting
confidence: 48%
“…There are some rare cases described in literature, in men, that had a late-onset at adult age and in which only one or two organ systems were affected. The kidneys (chronic kidney disease), and the cardiovascular system (hypertrophic cardiomyopathy, valvular anomalies, conduction disorders) were most frequently affected 19,20 . Our patient had no clinical or paraclinical evidence of a kidney or heart abnormalities.…”
Section: Hiv-associated Dementia Is Associated With a Symmetrical Pementioning
confidence: 99%
“…In line with these clinical findings, recent advanced MRI studies have showed the presence of a deeper and complex brain involvement in FD patients, with particular reference to the motor system [4]. Indeed, an alteration of the corticostriatal pathway has been described in FD patients, and a reduced functional connectivity between the motor cortex and the striatum has been described in this condition [5].…”
Section: Introductionmentioning
confidence: 61%
“…For this reason, future longitudinal studies are warranted to further confirm or dismiss this hypothesis. Another limitation of the present study is the absence of other specific vascular markers, such as the evaluation of the diameters of the brain’s posterior circulation, which have been reported as increased in FD patients [32]. Future studies correlating different imaging biomarkers are therefore warranted to evaluate a possible relation between these changes.…”
Section: Discussionmentioning
confidence: 98%